Animated Learning Video as a Supplementary Media in Teaching Recount Text - I Gusti Ayu Agung Bintang Permatasari; Ni Made Ratminingsih; Ni Putu Astiti Pratiwi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Technology is an essential factor that has a significant impact on improving aspects of human life, especially in education. Applying the Technological Pedagogical Content Knowledge (TPACK) is a must done by the teacher in this era to create a meaningful teaching and learning process. However, not all teachers can integrate their technical knowledge into the learning activity. The practical thing that can be done to apply the technological knowledge possessed by a teacher to create effective learning using technology is developing a learning media, especially in the form of an animated learning video. This study aimed to develop an animated learning video as a supplementary media in teaching recount text for grade 8 junior high school students and analyse the quality of the product. This design and development study used the modified ADDIE model, which included the analysis, design, development, and evaluation stages. The observation, interview, and questionnaire methods were used as the data collection methods of the study. The data analysis techniques used were qualitative descriptive analysis and quantitative descriptive analysis. The study indicated that based on the learning content expert test, the validation percentage result was 87,5% which was a good qualification. Meanwhile, based on the learning media expert test, the validation percentage result was 95%, an outstanding qualification. Therefore, the animated learning video is feasible to be used in the learning process. The research implication is that the animated learning video can help students grasp the material in the learning process.